Demographic and Epidemiological development in the Czech Republic and selected countries in the COVID-19 period. - Leigh, Oluwatosin Oluwafemi (2023)
The COVID-19 phenomenon took the whole world by surprise. This was a novel virus whose infectious rate was super high and worse of all; it had no known cure or vaccine at that time. Mostly affected were the elderly, and the young with underlying health conditions like High Blood pressure, Asthma, Diabetes etc. But given the high number already quoted by the various statistical bodies around the world, and the high number of adults living with underlying health challenges even before the COVID-19 outbreak, it is difficult to confirm the actual number of mortalities from COVID -19. Did all these people die from COVID -19 or their health challenges? Are the numbers quoted by statistical institutions overrated? Will these people have died anyway even without COVID -19? Is all excess mortality death from COVID-19? Is death from COVID -19 same as death with COVID -19? Why did some countries experience reduced deaths while some had more reported deaths? This paper attempts to provide some answers by evaluating the information provided by the concerned bodies. We reviewed the data provided by WHO and John Hopkins University, in a bid to draw comparisms and see any similarities. We also dived deep into excess mortality, in a bid to confirm if the excess mortality was because of COVID -19. While investigations suggest same in some countries, in order countries, it was not too obvious. We used descriptive and inferential analysis methods to review the pattern of excess mortality in selected geographical areas.